Impression Management Dokter di RSUD Kab Tangerang - Wiyanie Putri Pangesty; Ani Yuningsih (Bandung Conference Series: Public Relations, 2022)
Abstract. Life according to dramaturgy theory is like a theater, a social interaction similar to a drama show, which presents a role. In playing the role of using verbal language and non-verbal behavior and wearing certain attributes. Social life is divided into the front region (front region), which refers to social events in which the individual is stylish in displaying his role and the back region. In this study, who were taken as informants were 2 doctors on duty at the RSUD Kab Tangerang Hospital. This research is limited to studying and analyzing the front stage and back stage in dramaturgy theory to determine the impression management that is formed. This type of research uses qualitative research with a dramaturgy approach. The result of this research is that the front stage is very influential when building impression management, because it is the first thing that can be seen and judged by the public. The front stage is also related to personal branding which is supported by the credibility and skills of a doctor to build impression management. The strategy carried out by the two informants was based on the aspect of self promotion, favor doing. Abstrak. Kehidupan menurut teori dramaturgi adalah ibarat teather, interaksi sosial yang mirip pertunjukan drama, yang menampilkan peran. Dalam memainkan peran menggunakan bahasa verbal dan perilaku non verbal dan mengenakan atribut tertentu. kehidupan sosial dibagi menjadi wilayah depan” (front region) yang merujuk peristiwa sosial bahwa individu bergaya menampilkan perannya dan wilayah belakang (back region). Dalam penelitian ini, yang diambil sebagai informan adalah 2 Dokter yang bertugas di RSUD Kab Tangerang . Penelitian ini dibatasi untuk mengkaji dan menganalisis panggung depan dan panggung belakang pada teori dramaturgi untuk mengetahu impression management yang terbentuk. Tipe penelitian ini memakai penelitian kualitatif dengan pendekatan dramaturgi. Hasil penelitian ini adalah panggung depan sangat mempengaruhi saat membangun impression management, karena hal itu menjadi hal yang pertama dapat dilihat dan dinilai oleh khalayak. Dalam panggung depan ini juga berkaitan dengan personal branding yang didukung dengan kredibilitas dan keterampilan seorang dokter untuk membangun impression management. Strategi yang dilakukan oleh kedua informan berdasarkan dari segi aspek self promotion, favor doing.